Analisis Perbandingan Efisiensi Bank Umum Syariah (BUS) dan Unit Usaha Syariah (UUS) dengan Metode Stochastic Frontier Analysis (SFA) Periode 2010-2014 - Kustanti, Hesti; Indriani, Astiwi (Diponegoro Journal of Management, 2016)
Efficiency is a parameter to measure the performance of a company or banking. This study was conducted to analyze the efficiency of Islamic banking in Indonesia is made up of Sharia Commercial Banks (BUS) and Sharia Business Unit (UUS) using SFA (Stochastic Frontier Analysis).The population of this research are 12 Sharia Commercial Banks and 22 Sharia Business Unit. Of the population, elected 10 Islamic Banks and 5 Sharia Business Unit with purposive sampling. Input variables used in this study is the operational cost, total assets and labor costs. While the output variable used is total financing. This study uses Stochastic Frontier Analysis (SFA) with the production function and the intermediation approach. SFA measurement results in the form of a score of 0-1, when getting close to 1, the more efficient the bank anyway. Independent sample t-test was used in this study to measure differences in the level of efficiency of each bank group.The results showed that in 2010-2014, Islamic banking has increased the efficiency of each period. The average value of efficiency there is a 0.43994 Sharia Commercial Banks and Sharia Business Unit amounted to 0.47654, so that it can be concluded that the UUS superior BUS. The results of hypothesis testing panel, that the total assets of a significant and positive effect on total financing, operating costs are not significant and positive effect on total financing, and labor costs are not significant and negative effect on total financing. The test results on the independent sample t-test showed that there is no significant difference between the level of efficiency BUS and UUS.